Adverse Events in Carotid Endarterectomy From a Medicolegal Perspective. (July 2014) - Svider, Peter F.; Vidal, Gian-Paul; Zumba, Osvaldo; Mauro, Andrew C.; Haser, Paul B.; Graham, Alan; Rahimi, Saum
Objectives: Characterize factors raised in carotid endarterectomy litigation. Methods: Outcomes, alleged causes of malpractice, and other factors were evaluated. Results: Of the 37 verdicts and settlements, defendants were not liable in 25 (67.5%) cases. Frequently reported complications included stroke (51.3%) and hypoglossal nerve injury (27.0%), with other complications including airway compromise, vocal cord injury, and death. No cases reported myocardial infarction. Cerebral monitoring was mentioned in 2 cases, while inadequate informed consent, delayed diagnosis, and requirement of additional surgery were alleged in numerous instances. Settlements and jury awards averaged US895 833 and US1.53 million, respectively. Conclusions: Stroke and hypoglossal nerve injury are the most frequently litigated complications, and mean damages awarded were considerable. Knowledge of issues raised in our analysis may be included in a comprehensive consent process, potentially minimizing liability and improving patient safety.